Handbook of gas sensor materials : Properties, advantages and shortcomings for applications - Korotcenkov, Ghenadii (New York : Springer, 2014)
The two volumes of Handbook of Gas Sensor Materials provide a detailed and comprehensive account of materials for gas sensors, including the properties and relative advantages of various materials. Since these sensors can be applied for the automation of myriad industrial processes, as well as for everyday monitoring of such activities as public safety, engine performance, medical therapeutics, and in many other situations, this handbook is of great value. Gas sensor designers will find a treasure trove of material in these two books.
Index 443-454p.
Keywords: Photonic crystals; Semiconductor nanostructures; Surface functionalizing; Nanofibers